Type 2 innate lymphoid cell counts are increased in patients with systemic sclerosis and correlate with the extent of fibrosis - Wohlfahrt, Thomas; Usherenko, Svetlana; Englbrecht, Matthias; Dees, Clara; Weber, Stefanie; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2016)
Objective Type 2 innate lymphoid cells (ILC2s), a recently identified population of lymphoid cells lacking lineage-specific receptors, promote type 2 immunity and tissue remodelling. However, the contributive role of ILC2s in the pathogenesis of systemic sclerosis (SSc) is unknown. We aimed to evaluate the levels and correlations with fibrotic manifestations in SSc. Methods 69 patients with SSc and 47 healthy controls were included. Blood samples and skin sections were analysed by flow cytometry and immunohistochemically by staining two complementary panels of markers. Results Dermal and circulating ILC2s were significantly elevated in patients with SSc compared with controls. Dermal, but not circulating ILC2s were activated. Stratification of the SSc population in patients with limited cutaneous SSc (lcSSc) and diffuse cutaneous SSc (dcSSc) demonstrated increased levels of ILC2s in both subgroups with significantly higher frequencies in dcSSc compared with lcSSc. Moreover, dermal and circulating ILC2 counts correlated closely with the modified Rodnan skin score and with the presence of pulmonary fibrosis. Conclusions ILC2 counts are elevated in patients with SSc and correlate with the extent of skin fibrosis and the presence of interstitial lung disease providing compelling evidence for profibrotic effect of ILC2s in SSc.
EVALuna2:13149